2004
DOI: 10.1124/jpet.103.058255
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction Underlying Carbachol-Induced Contraction of Rat Urinary Bladder. II. Protein Kinases

Abstract: We have investigated the role of several protein kinases in carbachol-stimulated, M 3 muscarinic receptor-mediated contraction of rat urinary bladder. Concentration-response curves for the muscarinic receptor agonist carbachol were generated in the presence of multiple concentrations of inhibitors of various protein kinases, their inactive controls, or their vehicles. Bladder contraction was not significantly inhibited by three protein kinase C inhibitors (chelerythrine, 1-10 M; calphostin C, 0.1-1 M; and 2-[1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 28 publications
2
38
1
Order By: Relevance
“…Our data differ from other reports of PI-PLC mediating rat and human bladder contraction (Fleichman et al, 2004;Schneider et al, 2004a,b). These reports concluded that bladder contraction via M 3 receptors largely depends on calcium entry through nifedipine-sensitive channels and activation of ROCK, whereas phospholipase D and store-operated calcium channels contribute in a minor way, and phospholipase C or PKC do not seem to be involved.…”
Section: Discussioncontrasting
confidence: 56%
“…Our data differ from other reports of PI-PLC mediating rat and human bladder contraction (Fleichman et al, 2004;Schneider et al, 2004a,b). These reports concluded that bladder contraction via M 3 receptors largely depends on calcium entry through nifedipine-sensitive channels and activation of ROCK, whereas phospholipase D and store-operated calcium channels contribute in a minor way, and phospholipase C or PKC do not seem to be involved.…”
Section: Discussioncontrasting
confidence: 56%
“…Recently, we have intensively characterized the signaling pathways underlying muscarinic receptor-mediated contraction of rat and human urinary bladder (Fleichman et al, 2004;Schneider et al, 2004a,b). In the present study, we have investigated the signal transduction underlying rat urinary bladder relaxation by the ␤-adrenergic agonist isoproterenol.…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrated high levels of Rho-kinase isoforms (I and II) in the bladder. Supporting a role for Rho-kinase in detrusor contraction, Fleichman et al (2004) demonstrated in the rat bladder that carbachol-induced contraction did not involve protein kinase C, phosphatidylinositol-3-kinase, tyrosine kinases, or extracellular signal-regulated kinases, but that Rhoassociated kinases were involved. In the human detrusor, Schneider et al (2004) confirmed that the muscarinic receptor subtype mediating carbachol-induced contraction was the M 3 receptor: They also demonstrated that the phospholipase C inhibitor U-73122 [1-[6-[[17␤-methoxyestra-1,3,5(10)-trien-17-yl]amino]hexyl]-1H-pyrrole-2,5-dione] did not significantly affect carbachol-stimulated bladder contraction, despite blocking IP 3 generation.…”
Section: Peripheral Targetsmentioning
confidence: 99%